Sosialisasi Literasi Pajak Penghasilan Pada Generasi Milenial Dikota Sungai Penuh - Syafrul Antoni; M. Karim; Nelly Patria; Halim; Karlini Oktarina (CV. Multi Kreasi Media, 2025)
This community service activity aims to improve tax literacy, particularly related to Income Tax (PPh), among the millennial generation. The program was implemented through four stages: preparation and planning, socialization implementation, simulation and Q&A, and evaluation. The preparation phase involved identifying information needs, which led to the development of visual and digital-based educational modules and media. Socialization was conducted both offline and online, using a communicative approach relevant to young adults' characteristics. Tax calculation and reporting simulations were carried out to enhance participants' practical understanding, followed by interactive question-and-answer sessions. Evaluation using pre-test and post-test methods showed a significant improvement in participants' understanding, with average scores increasing from 52 to 84. The activity received positive feedback, with most participants expressing increased confidence in fulfilling their tax obligations independently. These results indicate that a communicative and applicative educational approach is effective in promoting voluntary tax compliance among millennials.